2007
DOI: 10.1088/0268-1242/22/6/010
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties and optical phonon frequencies of zinc-blende ScxGa1−xN

Abstract: Based on the empirical pseudopotential method within the virtual crystal approximation combined with the Harrison bond-orbital model, the elastic and lattice vibration properties of GaN, ScN and their hypothetical semiconducting alloys Sc x Ga 1−x N in the zinc-blende structure have been investigated. Quantities such as elastic constants, bulk modulus, shear modulus, refractive index, dielectric constants and optical phonon frequencies were calculated as a function of the scandium molar fraction x. The agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…2 and we will use them in the following analysis for consistency. A comparison with previous DFT-GGA literature data 21,22,40,41,43,44,49 yields, apart from a few exceptions, a good agreement with our results. The local density approximation (LDA) based C 11 elastic constants from the literature 20,42,47 are higher than our GGA-based data.…”
Section: B Single Crystal Elastic Constantssupporting
confidence: 91%
“…2 and we will use them in the following analysis for consistency. A comparison with previous DFT-GGA literature data 21,22,40,41,43,44,49 yields, apart from a few exceptions, a good agreement with our results. The local density approximation (LDA) based C 11 elastic constants from the literature 20,42,47 are higher than our GGA-based data.…”
Section: B Single Crystal Elastic Constantssupporting
confidence: 91%
“…1(a) it can be found that when the films are doped with Sc, the diffraction intensity of (002) peak remarkably decreases and the peak shifts to the low angle side. Generally, the AlN has the wurtzite structure while the ScN has the rock-salt (nonpolar) [21][22][23][24]. When Sc was doped into AlN films, the Sc atoms were substituted on the Al sub-lattice.…”
Section: Resultsmentioning
confidence: 99%
“…These results are utilized further to calculate frequency independent refractive index (n) using Moss relation [7]. The elastic constants c 11 , c 12 , c 44 and bulk modulus B are calculated following the method of Baranowski [8]. The static (H 0 ) and high frequency (H f ) dielectric constants are evaluated combining EPM with Harrison model [8].…”
Section: Theory and Computationmentioning
confidence: 99%
“…The elastic constants c 11 , c 12 , c 44 and bulk modulus B are calculated following the method of Baranowski [8]. The static (H 0 ) and high frequency (H f ) dielectric constants are evaluated combining EPM with Harrison model [8]. Pressure derivatives of static and high frequency dielectric constants can be obtained as [9]: (1)…”
Section: Theory and Computationmentioning
confidence: 99%
See 1 more Smart Citation